Kants Begriff der Verbindlichkeit und die neuzeitliche Naturrechtslehre - Hüning D. (Кантовский сборник, 2015)
My article is devoted to one of the main concepts of early modern natural law, i. e. the concept of obligation. Starting with Pufendorf's concept of obligation, it will be demonstrated that the natural law is grounded on the will of God. In contrast, the concept of obligation in Christian Wolff's Philosophia practica universalis has no need to found the validity of obligation of natural law in God's will. Instead he developed a concept which was based on the idea of a free self-binding moral subject. Therefore, Wolff's Philosophy has a great impact on Kant's own moral philosophy and especially on his concept of obligation. I will conclude by showing to what extent Kant was going beyond the early modern concept of the natural law tradition.